2010
DOI: 10.1002/eqe.1072
|View full text |Cite
|
Sign up to set email alerts
|

The existence of ‘complete similarities’ in the response of seismic isolated structures subjected to pulse‐like ground motions and their implications in analysis

Abstract: In this paper the seismic response of isolated structures supported on bearings with bilinear and trilinear behavior is revisited with dimensional analysis in an effort to better understand the relative significance of the various parameters that control the mechanical behavior of isolation systems. An isolation system that consists of lead rubber bearings or of single concave spherical sliding bearings exhibits bilinear behavior; whereas, when a double concave configuration is used the behavior is trilinear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Recently, Makris and Vassiliou 24 have shown that for most practical configurations the area of the shaded triangles shown in Figure 10 (right) is immaterial to the peak response of an isolated deck; therefore, the deck exhibits merely the same maximum displacement regardless whether it is supported on a double concave ( R 1 − h 1 , R 2 − h 2 , µ 1 , µ 2 ) or single concave ( R e , µ e ) spherical sliding bearing provided that and The aim of this analysis is to examine whether the selection of a lower coefficient of friction in one sliding surface may increase the merit of seismic isolation to protect rocking structures. The friction coefficients of two alternative DCSS systems are selected so that their equivalent coefficient of friction given by Equation (39) is µ e = 5%.…”
Section: Rocking Response Of a Rigid Block Standing Free On A Seismicmentioning
confidence: 99%
“…Recently, Makris and Vassiliou 24 have shown that for most practical configurations the area of the shaded triangles shown in Figure 10 (right) is immaterial to the peak response of an isolated deck; therefore, the deck exhibits merely the same maximum displacement regardless whether it is supported on a double concave ( R 1 − h 1 , R 2 − h 2 , µ 1 , µ 2 ) or single concave ( R e , µ e ) spherical sliding bearing provided that and The aim of this analysis is to examine whether the selection of a lower coefficient of friction in one sliding surface may increase the merit of seismic isolation to protect rocking structures. The friction coefficients of two alternative DCSS systems are selected so that their equivalent coefficient of friction given by Equation (39) is µ e = 5%.…”
Section: Rocking Response Of a Rigid Block Standing Free On A Seismicmentioning
confidence: 99%
“…The behaviour of the bilinear isolator is intrinsically determined by three parameters, which can be selected as V 0 , u y , and k p . u y was reported in earlier studies (eg, ) to have a minor impact on the maximum inelastic response; herein, a constant value associated with different groups of yielding isolators was introduced in order to capture more accurately the peak response, and at the same time limit the complexity of the proposed GDEs. In addition, u y was considered constant for different values of the post‐yield stiffness k p (ie, instead of assuming a constant ratio of k e / k p ) resulting to an initial stiffness ( k e = V 0 / u y + k p ) that is directly proportional to the yield strength ( V y = k e u y ) (ie, k e and V y expressed as functions of V 0 , u y , k p to define the bilinear hysteresis for modelling purposes).…”
Section: Analysis Frameworkmentioning
confidence: 99%
“…Strong ground motions often contain a distinguishable acceleration pulse, which is responsible for most of the inelastic deformation of fixed-base structures [58][59][60]. Physically realizable ground motion analytical pulses can qualitatively describe the impulsive character of near-fault ground motions.…”
Section: Dimensional Analysis Of the Rocking Podium Structure Modelmentioning
confidence: 99%